Penggunaan Huruf Ba Dalam Al-Qur'an Dan Implikasinya Bagi Pembelajaran Terjemah (Analisis Fungsi dan Makna Huruf Ba dalam Surat Ali Imran) - Aziz Ferdinan Irhas; Mustajab M Making (PT. Student Rihlah Indonesia, 2025)
Effective communication relies heavily on understanding the meaning of words. Unfortunately, understanding the Qur'an is often incomplete. The data understanding of the letter